Temporal effects of vascular endothelial growth factor and 3, 5‐cyclic monophosphate on blood–brain barrier solute permeability in vivo. Issue 12 (28th July 2014) - Shi, Lingyan; Zeng, Min; Fu, Bingmei M.
<x xml:space="preserve">Abstract</x> To test the hypothesis that vascular endothelial growth factor (VEGF) can transiently increase the blood–brain barrier permeability, P, as for peripheral microvessels and that the elevation of 3, 5‐cyclic monophosphate (cAMP) levels can inhibit the VEGF‐induced acute hyperpermeability, we employed multiphoton microscopy to quantify the cerebral microvessel permeability P to various‐sized solutes under VEGF and cAMP treatments. The cerebral microcirculation was observed through a section of frontoparietal bone thinned with a microgrinder. Fluorescein (MW 376Da), fluorescein isothioyanate‐dextran‐20k (FITC‐Dex‐20k), FITC‐Dex‐70k, or Alexa Fluor 488‐IgG in 1% bovine serum albumin mammalian Ringer's solution was injected into the cerebral circulation via the ipsilateral carotid artery with a syringe pump. Simultaneously, temporal images were collected from the brain parenchyma ∼100–200 μm below the pia mater. P was determined from the rate of tissue solute accumulation around individual microvessels. Exposure to 1 nM VEGF transiently increased P to 2.2, 10.5, 9.8, and 12.8 times control values, for fluorescein, Dex‐20k, Dex‐70k, and IgG, respectively, within 30 sec, and all returned to control levels within 2 min. After 20 min of pretreatment with 2 mM of the cAMP analog 8‐bromo‐cAMP, the initial increase by 1 nM VEGF was completely abolished in P of all solutes. The response pattern of P to VEGF and cAMP and the ratios of the peak to control values for rat cerebral microvessels are similar to those for rat mesenteric (peripheral) microvessels, except that the ratios are higher in P of cerebral microvessels for the intermediate and large solutes. These results imply a new approach for delivering large therapeutic agents to the brain. © 2014 Wiley Periodicals, Inc.